2003
DOI: 10.1096/fj.02-0908fje
|View full text |Cite
|
Sign up to set email alerts
|

Allergic humans are hypo‐responsive to CXCR3 chemokines in a Th1 immunity‐promoting loop

Abstract: CXCR3 binding chemokine CXCL10 (IP-10) markedly enhances antigen-specific Th1 recall responses in healthy humans, suggesting a role for this pathway in maintenance of clinical tolerance to environmental allergens as well as a potential therapeutic role for CXCR3 ligands in re-balancing the Th2-dominated responses that underlie generation and maintenance of allergic disorders. Here, we investigated the capacity of CXCR3 ligands to modulate allergen-driven IFNgamma production by healthy and allergic individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 53 publications
4
63
0
Order By: Relevance
“…It has been postulated that CXCL10 may be relevant in human immune responses not only for its role in the chemotaxis of T cells to inflammatory sites but also for regulating the expression of cytokine synthesis patterns. Furthermore, CXCL10 binding to its receptor was found to act as a costimulus with antigen, resulting in substantially enhanced IFN-␥ production, which inhibited T-cell proliferation (11). In the present study, we also observed a significant increase in IFN-␥ production in L. amazonensis-primed, CXCL10-treated CD4 ϩ T cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…It has been postulated that CXCL10 may be relevant in human immune responses not only for its role in the chemotaxis of T cells to inflammatory sites but also for regulating the expression of cytokine synthesis patterns. Furthermore, CXCL10 binding to its receptor was found to act as a costimulus with antigen, resulting in substantially enhanced IFN-␥ production, which inhibited T-cell proliferation (11). In the present study, we also observed a significant increase in IFN-␥ production in L. amazonensis-primed, CXCL10-treated CD4 ϩ T cells (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…CXCL10 secretion potentiates the Th1 immunity-promoting inflammatory loop, driven by the recruited CD4 C T lymphocytes at inflammation sites, supporting T-cell proliferation and IFNg secretion (Campbell et al 2004, Romagnani et al 2004. It is well known that TNFa synergizes with IFNg, modulating a number of different biological effects (Krakauer & Oppenheim 1993).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table II ϩ , CD45 RO ϩ ), but they rather exhibit a central memory profile (CD62L ϩ CCR7 ϩ ). They also express CXCR3, a chemokine receptor that has been reported to enhance allergen-specific IFN-␥ production (34). (Fig.…”
Section: T Cells In Allergic and Nonallergic Individualsmentioning
confidence: 99%